Ultra-low adhesion coating with anti-sticking and self-oil-seepage characteristics as well as preparation method and application of ultra-low adhesion coating

Through a one-step coating process, an ultra-low adhesion coating with anti-adhesion and self-oiling properties is formed on the surface of the substrate, which solves the problems of easy damage and insufficient adhesion of existing coatings, and achieves efficient and low-cost coating preparation and Excellent anti-stick performance.

CN119192996AActive Publication Date: 2024-12-27NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411598630.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2024-12-27
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing superhydrophobic coatings are susceptible to mechanical damage in practical applications, lack of adhesion, and the self-infiltrating surface preparation method is complex and costly, making it difficult to improve the coating adhesion while ensuring anti-adhesion and self-infiltrating characteristics.

Method used

By using a one-step coating process, a coating mixture of vinyl-terminated polydimethylsiloxane prepolymer, hydrogen-containing silicone oil, platinum catalyst and low molecular weight dimethylsiloxane oil are mixed on the surface of the substrate to form an anti-adhesion , ultra-low adhesion coating with self-infiltrating oil characteristics, and a stable cross-linking network structure is formed during the curing process.

Benefits of technology

Simple and efficient coating preparation is achieved, which significantly improves anti-adhesion properties and self-oiling properties, enhances the adhesion between the coating and the substrate, extends service life, and reduces production costs and time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192996A_ABST
    Figure CN119192996A_ABST
Patent Text Reader

Abstract

The invention provides an ultra-low adhesion coating with anti-sticking and self-oil-seepage characteristics as well as a preparation method and application thereof. The preparation method of the ultra-low adhesion coating comprises the following steps: cleaning the surface of a base material; the preparation method comprises the following steps: preparing a coating mixture containing a self-oil-seepage component: mixing a vinyl-terminated polydimethylsiloxane prepolymer, hydrogen-containing silicone oil, low-molecular-weight dimethyl silicone oil and a platinum catalyst in proportion, stirring, degassing in a vacuum environment, and curing to form an ultralow-adhesion coating with anti-adhesion and self-oil-seepage characteristics; the preparation method is simple and convenient in process, an ultra-low adhesion coating with anti-adhesion and self-oil-seepage characteristics can be formed on the surfaces of various base materials, and the ultra-low adhesion coating has high adhesive force with the base materials; in addition, according to the silicone rubber adhesion method based on the coating, the binding force of the silicone rubber and the base material is remarkably improved, the production efficiency is effectively improved, the production cost is reduced, and good industrial application value is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional coating materials, and in particular to an ultra-low adhesion coating with anti-sticking and self-oil seepage properties, and a preparation method and application thereof. Background Art

[0002] Anti-stick coating materials have a wide range of applications in the fields of industry, medical treatment, food processing, marine engineering, etc., such as preventing adhesion, reducing friction, easy to clean and reducing biofouling. At present, super-hydrophobic coatings and low surface energy materials are widely used to achieve anti-stick effects. These coatings usually reduce the surface energy by constructing micro-nano structures on the surface of the substrate or introducing fluoropolymers, thereby reducing the adhesion of substances. However, traditional super-hydrophobic coatings have some limitations in practical applications. First, the micro-nano structures of these coatings are susceptible to mechanical damage, resulting in decreased anti-stick properties. Secondly, the use of fluoropolymers may bring environmental and health concerns. In addition, most anti-stick coatings have insufficient adhesion to the surface of the substrate and are easy to fall off, affecting their long-term use.

[0003] In order to overcome the defects of superhydrophobic coatings, self-penetrating oil surfaces (SLIPS, slippery liquid wetted surfaces) have been proposed and attracted widespread attention. Self-penetrating oil surfaces can effectively inhibit the adhesion of substances by introducing lubricating liquid into the porous structure to form a stable thin liquid layer. Self-penetrating oil surfaces have excellent anti-stick and self-lubricating properties, and have a certain self-repair ability for surface damage.

[0004] However, current methods for preparing self-penetrating oil surfaces usually involve complex multi-step processes, such as the construction of porous structures, the injection and retention of lubricating fluids, etc. These methods are often complex, costly, and inefficient. In addition, the loss and evaporation of lubricating fluids can also cause the anti-sticking properties to decrease over time. On the other hand, how to improve the adhesion of the coating on the substrate while ensuring the anti-sticking and self-penetrating oil properties is still a technical problem that needs to be solved urgently.

[0005] Therefore, there is an urgent need for a simple and efficient coating preparation method that can give the material anti-stick, self-oil permeability properties and high adhesion to meet the needs of practical applications. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a simple and efficient coating preparation method, which can construct an ultra-low adhesion coating with both anti-stick and self-oil permeation properties, and the coating has high adhesion to the substrate to meet practical application requirements.

[0007] According to the present invention, a method for preparing an ultra-low adhesion coating with anti-sticking and self-oiling properties is provided, comprising the following steps: Substrate pretreatment: Clean the surface of the substrate; Preparing a coating mixture containing a self-seeping oil component: mixing a vinyl-terminated polydimethylsiloxane prepolymer, a hydrogenated silicone oil, a platinum catalyst and a low molecular weight dimethyl silicone oil in proportion, stirring to obtain a uniform coating mixture, and vacuum degassing the mixture to obtain a uniform coating mixture containing a self-seeping oil component; Applying an ultra-low adhesion self-penetrating oil coating: After applying a coating mixture containing a self-penetrating oil component on the pretreated substrate surface, it is placed in an oven and cured at 60-150°C for 30-120 minutes to form an ultra-low adhesion coating with both anti-stick and self-penetrating oil properties on the substrate surface.

[0008] As a further illustration of the present invention, during the substrate pretreatment process, the substrate is ultrasonically cleaned for 5 to 15 minutes each time using acetone, anhydrous ethanol and deionized water in sequence to remove surface oil and impurities, and then dried in a clean environment for later use.

[0009] As a further illustration of the present invention, in the process of preparing the coating mixture containing the self-seeping oil component, the vinyl-terminated polydimethylsiloxane prepolymer and the hydrogen-containing silicone oil are mixed in a mass ratio of 100:(8-12), a small amount of platinum catalyst is added and mixed evenly, and then the low molecular weight dimethyl silicone oil is added, and the mass fraction of the low molecular weight dimethyl silicone oil in the coating mixture is 30%-70%; the molecular weight of the vinyl-terminated polydimethylsiloxane prepolymer is 5,000-20,000 g / mol; the hydrogen content of the hydrogen-containing silicone oil is 0.5-2.0 mmol / g; the platinum content of the platinum catalyst is 0.1-2 wt%; the viscosity of the low molecular weight dimethyl silicone oil is 5-200 cSt.

[0010] As a further illustration of the present invention, in the process of preparing the coating mixture containing the self-penetrating oil component, the stirring temperature is 20-40°C, the stirring time is 0.5-2 hours, the vacuum degree of vacuum degassing is 1-100 Pa, and the degassing time is 10-60 minutes.

[0011] As a further illustration of the present invention, the coating method in the process of coating the ultra-low adhesion self-penetrating oil coating is one of spin coating, spray coating, scraper coating, dip coating or screen printing; In the process of coating the coating mixture containing the self-penetrating oil component on the surface of the pretreated substrate, the substrate is placed in an environment with a vacuum degree of 1-100 Pa for degassing for 5-30 minutes before coating; the coating thickness after coating is 5-100 μm.

[0012] As a further illustration of the present invention, the material of the substrate is one of stainless steel, aluminum alloy, glass, ceramic, silicon wafer, polycarbonate, polypropylene or polyimide.

[0013] The present invention also provides an ultra-low adhesion coating prepared by the above method and having anti-sticking and self-oil seeping properties.

[0014] The present invention also provides the use of the above-mentioned ultra-low adhesion coating with anti-sticking and self-oil seepage characteristics in improving the adhesion of silicone rubber coating.

[0015] As a further illustration of the present invention, an ultra-low adhesion coating with anti-stick and self-oiling properties is introduced between the substrate and the silicone rubber coating.

[0016] As a further illustration of the present invention, in the process of introducing an ultra-low adhesion coating between a substrate and a silicone rubber coating, a coating mixture of a self-seeping oil component is first coated on the pretreated surface of the substrate, the coating thickness of which is 5 to 50 μm, and after degassing for 5 to 30 minutes under a vacuum condition of 1 to 100 Pa, the coating is cured at 60 to 150° C. for 1 to 15 minutes to obtain an interface layer containing a self-seeping oil component, and then a silicone rubber material with a thickness of 5 to 100 μm is coated on the interface layer, and the coating is cured at 100 to 150° C. for 30 to 120 minutes to obtain a silicone rubber coating with high bonding strength.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. Simple and efficient one-step coating process: The present invention adopts a one-step coating process to integrate multiple functions such as anti-sticking, self-penetration and high adhesion into a single coating. This method significantly simplifies the traditional multi-layer coating process and greatly reduces production costs and time. At the same time, one-step coating also reduces interlayer interface problems and improves the overall performance and stability of the coating.

[0018] 2. Excellent anti-sticking performance and self-penetrating properties: By introducing low molecular weight dimethyl silicone oil into the coating mixture, the present invention successfully combines anti-sticking performance and self-penetrating properties. This unique combination not only makes the coating surface have ultra-low adhesion, but also can quickly repair the surface performance through the self-penetrating mechanism when worn or slightly damaged, significantly extending the service life and reliability of the coating.

[0019] 3. High adhesion and wide applicability to substrates: The coating formula design of the present invention takes into account the bonding strength with the substrate. By adjusting the ratio of PDMS prepolymer, hydrogenated silicone oil and low molecular weight dimethyl silicone oil, and adopting appropriate substrate pretreatment methods, the coating can form a strong bond with a variety of substrates (such as metal, glass, ceramics and polymer materials, etc.). This greatly expands the application range of the coating and meets the needs of different fields.

[0020] 4. Excellent high temperature resistance: The organic silicon material used in the present invention has excellent high temperature resistance. Through a carefully designed curing process (curing at 60-150°C for 30-120 minutes), the coating forms a stable cross-linked network structure. This allows the coating to maintain its functional properties such as anti-sticking and self-oiling under high temperature environments, greatly expanding its application potential under harsh conditions, such as high temperature baking equipment, heat exchanger surface treatment and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings of the embodiments will be briefly described below. It should be noted that the drawings described below only relate to some embodiments of the present disclosure, but are not intended to limit the present disclosure, wherein: Figure 1 It is a comparison diagram of the ultra-low adhesion coating with anti-sticking and self-oiling properties prepared on stainless steel provided in Example 1 of the present invention.

[0022] Figure 2 It is the AFM data diagram of the stainless steel sheet sample prepared in Example 1 of the present invention and its adhesion result.

[0023] Figure 3 These are the interference fringes of the oil film on the surface of the stainless steel sheet sample prepared in Example 2 of the present invention.

[0024] Figure 4 This is a comparison chart of the T-type 3M tape peeling force of the aluminum alloy sheet samples prepared in Example 4 of the present invention.

[0025] Figure 5 This is the peeling effect of ASTM D3359 adhesion on a glass sheet in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution of the embodiments of the present disclosure will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by those skilled in the art without creative work also fall within the scope of protection of the present disclosure.

[0027] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by a person skilled in the art to which the subject matter of the present disclosure belongs. It will be further understood that terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the specification and the relevant art, and will not be interpreted in an idealized or overly formal form unless otherwise explicitly defined herein. As used herein, a statement that two or more parts are "connected" or "coupled" together shall mean that the parts are joined together directly or through one or more intermediate components.

[0028] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiments" in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0029] The present invention provides a method for preparing an ultra-low adhesion coating with anti-sticking and self-oil permeation properties, comprising the following steps: Substrate pretreatment: clean the surface of the substrate; use acetone, anhydrous ethanol and deionized water to ultrasonically clean the substrate for 5 to 15 minutes each time to remove surface oil and impurities, and dry it in a clean environment after cleaning; In some embodiments of the present invention, the substrate pretreatment process may also be plasma treatment or chemical immersion treatment, wherein the chemical immersion treatment uses 1% to 10% NaOH or HCl solution for 5 to 10 minutes; Preparing a coating mixture containing a self-seeping oil component: mixing a vinyl-terminated polydimethylsiloxane prepolymer, a hydrogenated silicone oil, a platinum catalyst and a low molecular weight dimethyl silicone oil in proportion, stirring to obtain a uniform coating mixture, and vacuum degassing the mixture to obtain a uniform coating mixture containing a self-seeping oil component; Wherein, the mass ratio of the vinyl terminated polydimethylsiloxane prepolymer to the hydrogen-containing silicone oil is preferably 100:(8-12), for example, it can be 100:8, 100:9, 100:10, 100:11, 100:12, and more preferably 100:10; the mass fraction of the low molecular weight dimethyl silicone oil in the coating mixture is preferably 30%-70%, for example, it can be 30%, 40%, 50%, 60%, 70%, and more preferably 50%; the molecular weight of the vinyl terminated polydimethylsiloxane prepolymer is preferably 5,000-20,000 g / mol, and the average molecular weight is preferably 8000-15000 g / mol, and more preferably 10000 g / mol; the hydrogen content of the hydrogen-containing silicone oil is preferably 0.5-2.0 mmol / g, for example, it can be 0.5 mmol / g, 0.8 mmol / g, 1.0 mmol / g, 1.5 mmol / g, 1.8 mmol / g, 2.0 mmol / g, more preferably 1.0 mmol / g; the platinum content of the platinum catalyst is preferably 0.1-2 wt%, for example, 0.1wt%, 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, more preferably 0.5wt%; the viscosity of the low molecular weight dimethyl silicone oil is preferably 5-200 cSt, and the average viscosity is preferably 50-150 cSt, more preferably 50 cSt; In the present invention, the stirring temperature during the mixing process is preferably 20 to 40° C., for example, 20° C., 25° C., 30° C., 35° C., or 40° C. The stirring time is preferably 0.5 to 2 hours, for example, 0.5 hour, 1.0 hour, 1.5 hour, or 2 hours. The vacuum degree of the vacuum degassing is 1 to 100 Pa, and the degassing time is preferably 10 to 60 minutes, for example, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or 60 minutes. Applying an ultra-low adhesion self-penetrating oil coating: After applying a coating mixture containing a self-penetrating oil component to the surface of the pretreated substrate, the coating mixture is placed in an oven and cured at 60 to 150° C. for 30 to 120 minutes, for example, 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C.; 30 minutes, 40 minutes, 60 minutes, 75 minutes, 90 minutes, 120 minutes, to form an ultra-low adhesion coating with both anti-sticking and self-penetrating oil properties on the surface of the substrate; In the curing process, the temperature can be raised in stages for curing. Specifically, the curing temperature is firstly 60 to 100° C. for 30 to 60 minutes, and then the curing temperature is 100 to 150° C. for 30 to 600 minutes.

[0030] In the present invention, in the process of coating the coating mixture containing the self-seeping oil component on the surface of the pretreated substrate, the substrate is placed in an environment with a vacuum degree of 1 to 100 Pa for degassing for preferably 5 to 30 minutes before coating, for example, it can be 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes; the coating thickness after coating is preferably 5 to 100 μm, for example, it can be 5 μm, 20 μm, 45 μm, 60 μm, 75 μm, 85 μm, 90 μm, 100 μm.

[0031] The ultra-low adhesion coating with anti-stick and self-oiling properties provided by the present invention is used to improve the adhesion of silicone rubber coating. The substrate can be glass, metal, ceramic or polymer material, and the silicone rubber material can be Sylgard® 184, Sylgard® 527, etc.

[0032] The following is explained in conjunction with specific embodiments: Embodiment 1: A method for preparing an ultra-low adhesion coating having both anti-sticking and self-oil permeation properties, the method comprising the following steps: S1: Substrate pretreatment A stainless steel substrate with a size of 200mm×50mm×2mm was selected as the experimental object. The substrate was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water in turn for 10 minutes each time to thoroughly remove surface oil and impurities. After cleaning, it was dried at room temperature in a clean environment for use. Furthermore, in order to enhance the adhesion between the coating and the substrate, the dried glass substrate was placed in a plasma cleaner and treated with oxygen plasma for 5 minutes, or the substrate was immersed in a 5% NaOH solution for 10 minutes. After treatment, it was fully rinsed with deionized water and dried for use.

[0033] S2: Preparation of coating mixture containing self-penetrating oil component Weigh 10g of vinyl-terminated polydimethylsiloxane prepolymer with a molecular weight of 10,000 g / mol. Weigh 1g of hydrogenated silicone oil with a hydrogen content of 1.0 mmol / g, so that the mass ratio of PDMS prepolymer to hydrogenated silicone oil is 100:10. Low molecular weight dimethyl silicone oil: Weigh 11g of low molecular weight dimethyl silicone oil with a viscosity of 50 cSt, so that its mass fraction in the coating mixture is 50%. Add an appropriate amount of platinum catalyst (about 0.1g) with a platinum content of 0.5 wt%.

[0034] All the above components were placed in a clean beaker and stirred at 25°C for 1 hour using a magnetic stirrer until a uniform coating mixture was formed. The uniformly stirred coating mixture was placed in a vacuum drying oven and degassed for 30 minutes at a vacuum degree of 50 Pa to remove bubbles in the mixture, thereby obtaining a coating mixture containing a self-penetrating oil component.

[0035] S3: Apply ultra-low adhesion self-penetrating oil coating The pretreated glass substrate was coated by spin coating. The coating mixture was dropped on the center of the substrate, and the spin coating parameters were set: the initial speed was 500 rpm, and the coating was evenly spread for 10 seconds; then the coating was rotated at 2000 rpm for 30 seconds, and the coating thickness was controlled to be about 20μm. After coating, the sample was placed in a vacuum environment (vacuum degree of 50 Pa) for degassing for 15 minutes to further eliminate tiny bubbles in the coating and ensure the density and flatness of the coating.

[0036] The degassed sample was placed in an oven and cured at 100°C for 60 minutes. During the curing process, hydrogenated silicone oil and PDMS prepolymer reacted under the action of platinum catalyst to form a cross-linked elastomer network, and low molecular weight dimethyl silicone oil was physically embedded in the network. After the curing was completed, the sample was taken out and cooled to room temperature. At this point, a layer of ultra-low adhesion coating with anti-sticking and self-penetrating properties has been formed on the surface of the substrate. Figure 1 The following is a sample image of a steel sheet constructed by the present invention. Figure 1 The top image shows PDMS without silicone oil added.

[0037] S4: Performance Evaluation The surface morphology of the coating was observed using an atomic force microscope (AFM), and it was found that the coating surface was flat and smooth without obvious defects. Figure 2 The right side shows the AFM adhesion test of the sample in Example 1, which is 15nN, much smaller than Figure 2 The PDMS sample on the left shows its excellent anti-adhesion performance.

[0038] A needle was used to scrape tiny scratches on the coating surface. After standing for 1 hour, the scratches were observed to gradually disappear, indicating that the low molecular weight dimethyl silicone oil migrated from the inside of the coating to the surface, achieving self-repair function.

[0039] Example 2

[0040] S1: Substrate pretreatment A 304 stainless steel sheet with a size of 100mm×100mm×1mm was selected as the experimental object. The substrate was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water in turn, each time for 8 minutes to thoroughly remove surface oil and impurities. After cleaning, it was dried at room temperature in a clean environment for use. In order to enhance the adhesion between the coating and the metal substrate, the dried stainless steel sheet was placed in a plasma cleaning machine and treated with argon plasma for 3 minutes. After treatment, it was rinsed with deionized water and dried for use.

[0041] S2: Preparation of coating mixture containing self-penetrating oil component Weigh 12g of vinyl-terminated polydimethylsiloxane prepolymer with a molecular weight of 15,000 g / mol. Weigh 1.2g of hydrogenated silicone oil with a hydrogen content of 1.5 mmol / g, so that the mass ratio of PDMS prepolymer to hydrogenated silicone oil is 100:10. Low molecular weight dimethyl silicone oil: Weigh 8g of low molecular weight dimethyl silicone oil with a viscosity of 100 cSt, so that its mass fraction in the coating mixture is 37.5%. Add 0.15g of platinum catalyst with a platinum content of 1 wt%.

[0042] Put all the above components into a clean beaker and stir them with a magnetic stirrer at 30°C for 1.5 hours until a uniform coating mixture is formed. Place the uniformly stirred coating mixture in a vacuum drying oven and degas for 45 minutes at a vacuum degree of 20 Pa to remove bubbles in the mixture.

[0043] S3: Apply ultra-low adhesion self-penetrating oil coating The pretreated stainless steel substrate was coated by spraying. A pneumatic spray gun was used, the spray pressure was set to 0.3 MPa, the spray distance was 15 cm, and the coating was evenly sprayed in an "8" shape. The coating thickness was controlled to be about 50 μm. After coating, the sample was placed in a vacuum environment (vacuum degree of 30 Pa) for degassing for 20 minutes to further eliminate tiny bubbles in the coating.

[0044] The degassed sample was placed in an oven and cured at 120°C for 90 minutes. After the curing was completed, the sample was taken out and slowly cooled to room temperature. At this point, an ultra-low adhesion coating with anti-stick and self-penetrating properties had been formed on the stainless steel surface.

[0045] S4: Performance Evaluation The surface morphology of the coating was observed using an atomic force microscope (AFM), and it was found that the coating surface was flat and smooth without obvious defects. The AFM adhesion test was 18nN, which is much smaller than Figure 2 The PDMS sample on the left shows its excellent anti-adhesion performance.

[0046] Use a needle to scratch a tiny scratch on the coating surface. After standing for 1.5 hours, the scratch gradually disappears, indicating that the low molecular weight dimethyl silicone oil migrates from the inside of the coating to the surface, achieving self-repairing function. Observe through an optical microscope. Figure 3 The thin film interference fringes of the oil film can be seen in the figure, indicating that there is a very thin oil film on the surface of the sample.

[0047] Example 3: S1: Substrate pretreatment A polycarbonate plate with a size of 80 mm × 80 mm × 3 mm was selected as the experimental object. The surface was gently wiped with a neutral detergent solution, and then rinsed with deionized water for 3 times. The surface was gently wiped with anhydrous ethanol using a dust-free cloth to remove residual stains. Dry at room temperature for 30 minutes in a clean environment for use. In order to enhance the adhesion of the coating to the polymer substrate, the dried polycarbonate plate was placed in a UV ozone cleaning machine for 2 minutes.

[0048] S2: Preparation of coating mixture containing self-penetrating oil component Weigh 8 g of vinyl-terminated polydimethylsiloxane prepolymer with a molecular weight of 8,000 g / mol. Weigh 0.72 g of hydrogenated silicone oil with a hydrogen content of 0.8 mmol / g, so that the mass ratio of PDMS prepolymer to hydrogenated silicone oil is 100:9. Low molecular weight dimethyl silicone oil: Weigh 13 g of low molecular weight dimethyl silicone oil with a viscosity of 20 cSt, so that its mass fraction in the coating mixture is 60%. Add 0.08 g of platinum catalyst with a platinum content of 0.3 wt%.

[0049] Put all the above components into a clean beaker and stir them with a magnetic stirrer at 25°C for 40 minutes until a uniform coating mixture is formed. Place the uniformly stirred coating mixture in a vacuum drying oven and degas for 25 minutes at a vacuum degree of 40 Pa to remove bubbles in the mixture.

[0050] S3: Apply ultra-low adhesion self-penetrating oil coating The pretreated polycarbonate substrate was coated by scraper coating. An automatic coating machine was used, the scraper height was set to 100 μm, and the coating was uniformly applied at a speed of 2 mm / s. The coating thickness was controlled to be about 30 μm. After coating, the sample was placed in a vacuum environment (vacuum degree of 50 Pa) for degassing for 10 minutes to further eliminate tiny bubbles in the coating.

[0051] The degassed sample was placed in an oven and cured at 80°C for 120 minutes. After the curing was completed, the sample was taken out and cooled naturally to room temperature. At this point, an ultra-low adhesion coating with anti-stick and self-penetrating properties had been formed on the polycarbonate surface.

[0052] S4: Performance Evaluation The surface morphology of the coating was observed using an atomic force microscope (AFM), and it was found that the coating surface was flat and smooth without obvious defects. The AFM adhesion test was 21.1nN, which is much smaller than Figure 2 The PDMS sample on the left shows its excellent anti-adhesion performance.

[0053] A needle was used to scratch tiny scratches on the coating surface. After standing for 1.5 hours, the scratches were observed to gradually disappear, indicating that the low molecular weight dimethyl silicone oil migrated from the inside of the coating to the surface, achieving self-repair function.

[0054] Example 4: S1: Substrate pretreatment A 6061 aluminum alloy sheet with a size of 70 mm × 70 mm × 2 mm was selected as the experimental object. The substrate was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water in turn, each for 12 minutes, to thoroughly remove surface oil and impurities. After cleaning, it was dried at room temperature in a clean environment for use. Further, the dried aluminum alloy sheet was immersed in a 3% HCl solution for 8 minutes to enhance the surface roughness and activity. After treatment, it was fully rinsed with deionized water and dried in a 60°C oven for 15 minutes for use.

[0055] S2: Preparation of coating mixture containing self-penetrating oil component Weigh 15g of vinyl-terminated polydimethylsiloxane prepolymer with a molecular weight of 12,000 g / mol. Weigh 1.65g of hydrogenated silicone oil with a hydrogen content of 1.2 mmol / g, so that the mass ratio of PDMS prepolymer to hydrogenated silicone oil is 100:11. Low molecular weight dimethyl silicone oil: Weigh 12g of low molecular weight dimethyl silicone oil with a viscosity of 80 cSt, so that its mass fraction in the coating mixture is 42%. Add 0.2g of platinum catalyst with a platinum content of 0.8 wt%.

[0056] Put all the above components into a clean beaker and stir them with a mechanical stirrer at 35°C for 55 minutes until a uniform coating mixture is formed. Place the uniformly stirred coating mixture in a vacuum drying oven and degas for 50 minutes at a vacuum degree of 15 Pa to remove bubbles in the mixture.

[0057] S3: Apply ultra-low adhesion self-penetrating oil coating The pretreated aluminum alloy substrate was coated by dip coating. The substrate was immersed in the coating mixture at a speed of 5 mm / s, and then taken out at the same speed after staying for 5 seconds. The coating thickness was controlled to be about 40 μm. After coating, the sample was placed in a vacuum environment (vacuum degree of 25 Pa) for degassing for 15 minutes to further eliminate the tiny bubbles in the coating.

[0058] The degassed sample was placed in an oven and cured at 110°C for 75 minutes. After the curing was completed, the sample was taken out and cooled at room temperature for 30 minutes. At this point, an ultra-low adhesion coating with anti-stick and self-penetrating properties had been formed on the aluminum alloy surface.

[0059] S4: Performance Evaluation The surface morphology of the coating was observed using an atomic force microscope (AFM), and it was found that the coating surface was flat and smooth without obvious defects. The AFM adhesion test was 13.7nN, which is much smaller than Figure 2 The PDMS sample on the left shows its excellent anti-adhesion performance.

[0060] The known samples were subjected to T-type peeling test with 3M-VHB tape, such as Figure 4 The peeling force of Example 4 was measured to be 0.566 gf / cm, which is smaller than that of common materials such as PDMS (5.30 gf / cm) and polytetrafluoroethylene (26.7 gf / cm).

[0061] Example 5: S1: Substrate pretreatment Alumina ceramic sheets with a size of 60mm×60mm×5mm were selected as experimental objects. The substrate was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 15 minutes each time to thoroughly remove surface oil and impurities. After cleaning, it was dried at 100℃ for 30 minutes in a clean environment for use. In order to enhance the adhesion between the coating and the ceramic substrate, the dried ceramic sheet was placed in a plasma cleaner and treated with oxygen plasma for 6 minutes. After treatment, it was rinsed with deionized water and dried in an oven at 80℃ for 20 minutes for use.

[0062] S2: Preparation of coating mixture containing self-penetrating oil component Weigh 9 g of vinyl-terminated polydimethylsiloxane prepolymer with a molecular weight of 18,000 g / mol. Weigh 0.99 g of hydrogenated silicone oil with a hydrogen content of 1.8 mmol / g, so that the mass ratio of PDMS prepolymer to hydrogenated silicone oil is 100:11. Low molecular weight dimethyl silicone oil: Weigh 7 g of low molecular weight dimethyl silicone oil with a viscosity of 150 cSt, so that its mass fraction in the coating mixture is 41%. Add 0.12 g of platinum catalyst with a platinum content of 1.5 wt%.

[0063] Put all the above components into a clean beaker and stir them with a mechanical stirrer at 28°C for 80 minutes until a uniform coating mixture is formed. Place the uniformly stirred coating mixture in a vacuum drying oven and degas for 60 minutes at a vacuum degree of 10 Pa to remove bubbles in the mixture.

[0064] S3: Apply ultra-low adhesion self-penetrating oil coating The pretreated ceramic substrate was coated by screen printing. A 200-mesh polyester screen was used, the squeegee hardness was 70 degrees, the printing pressure was 0.4 MPa, and the printing speed was 100 mm / s. The coating thickness was controlled to be about 25 μm. After coating, the sample was placed in a vacuum environment (vacuum degree of 35 Pa) for degassing for 25 minutes to further eliminate the tiny bubbles in the coating.

[0065] The degassed sample was placed in an oven and cured at 135°C for 60 minutes. After curing, the temperature was slowly lowered to room temperature at a rate of 1°C / min. At this point, an ultra-low adhesion coating with anti-stick and self-penetrating properties had been formed on the ceramic surface.

[0066] S4: Performance Evaluation The surface morphology of the coating was observed using an atomic force microscope (AFM), and it was found that the coating surface was flat and smooth without obvious defects. The AFM adhesion test was 17.3nN, which is much smaller than Figure 2 The PDMS sample on the left shows its excellent anti-adhesion performance.

[0067] The known samples were subjected to T-type peeling test with 3M-VHB tape, such as Figure 4 The peeling force of Example 4 was measured to be 0.610 gf / cm, which is smaller than that of common materials such as PDMS (5.30 gf / cm) and polytetrafluoroethylene (26.7 gf / cm).

[0068] A needle was used to scrape tiny scratches on the coating surface. After standing for 2 hours, the scratches were observed to gradually disappear, indicating that the low molecular weight dimethyl silicone oil migrated from the inside of the coating to the surface, achieving self-repair function.

[0069] Embodiment 6: A method for using a silicone rubber surface layer with high bonding strength: S1: Substrate surface preparation A steel substrate with a size of 200mm×50mm×2mm was selected as the experimental object. The substrate was ultrasonically cleaned with acetone, anhydrous ethanol and deionized water in turn, each time for 10 minutes to thoroughly remove surface oil and impurities. The dried glass substrate was placed in a plasma cleaner and treated with oxygen plasma for 5 minutes to improve surface activity and enhance coating adhesion.

[0070] S2: Coating of interface layer containing self-penetrating oil component Weigh 10 g of vinyl-terminated polydimethylsiloxane prepolymer with a molecular weight of 10,000 g / mol. Weigh 1 g of hydrogenated silicone oil with a hydrogen content of 1.0 mmol / g, so that the mass ratio of PDMS prepolymer to hydrogenated silicone oil is 100:10. Weigh 5 g of low molecular weight dimethyl silicone oil with a viscosity of 50 cSt, so that its mass fraction in the mixture is 33%. Add 0.1 g of platinum catalyst with a platinum content of 0.5 wt%. Place the above components in a clean beaker and stir at 25°C for 1 hour until a uniform coating mixture is formed. Place the mixture in a vacuum drying oven and degas for 30 minutes at a vacuum degree of 50 Pa to remove bubbles in the mixture.

[0071] The coating mixture was dropped onto the center of the substrate using the spin coating method. The spin coating parameters were set as follows: initial speed of 500 rpm for 10 seconds; then 2000 rpm for 30 seconds, and the coating thickness was controlled to be approximately 20 μm. After coating, the sample was placed in a vacuum environment (vacuum degree of 50 Pa) for degassing for 15 minutes. The sample was placed in an oven and cured at 100 ° C for 15 minutes to form an interfacial layer containing self-penetrating oil components.

[0072] S3: Silicone rubber surface coating Take the silicone rubber material Sylgard® 184, mix it in a mass ratio of 10:1 between the base and the curing agent, and stir it thoroughly for 30 minutes until it is uniform. Apply the silicone rubber solution on the cured interface layer, and use the scraping method to control the coating thickness to be about 50μm. After coating, place the sample in a vacuum environment (vacuum degree of 50 Pa) for degassing for 20 minutes to remove bubbles in the coating. Put the sample in an oven and cure it at 120℃ for 60 minutes to form a silicone rubber surface layer with high bonding strength.

[0073] S4: Performance Evaluation Adhesion test: According to ASTM D3359 standard, such as Figure 5 The adhesion test using the cross method is shown on the right. The result is 5B, indicating that the coating has excellent adhesion to the substrate.

[0074] Comparative Example 1: A method for coating silicone rubber without using an interface layer is carried out according to the following steps: S1: Substrate surface preparation The same cleaning and plasma treatment are performed as in step S1 of Example 6.

[0075] S2: Directly coat the silicone rubber surface layer Same as step S3 of Example 6. Directly coat the silicone rubber solution on the pretreated substrate surface to a thickness of about 50 μm. Degas in a vacuum environment for 20 minutes. Curing at 120° C. for 60 minutes to form a silicone rubber surface layer.

[0076] S3: Performance Evaluation Adhesion test: According to ASTM D3359 standard, such as Figure 5 The left-scratch X test result was 2B, with severe coating peeling and poor adhesion.

[0077] In summary: By introducing an interface layer containing a self-penetrating oil component between the substrate and the silicone rubber surface layer (Example 6), the adhesion and peel strength of the silicone rubber coating are significantly improved. Compared with Example 6 and Comparative Example 1, the coating in Example 6 reaches 5B grade in the adhesion test, and the interface bonding is more firm.

[0078] This method for preparing a silicone rubber surface layer with high bonding strength is not only simple in process and highly operable, but also does not require the use of additional adhesives, reducing process steps and material costs. This method is applicable to various substrates, such as glass, metal, ceramic and polymer materials, and has broad application prospects. It can be used in biomedical devices, electronic packaging, flexible sensors and other fields, and is of great significance to improving product reliability and service life.

[0079] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing an ultra-low adhesion coating with anti-sticking and self-oiling properties, characterized in that: The preparation method comprises the following steps: Substrate pretreatment: Clean the surface of the substrate; Preparing a coating mixture containing a self-seeping oil component: mixing a vinyl-terminated polydimethylsiloxane prepolymer, a hydrogenated silicone oil, a platinum catalyst and a low molecular weight dimethyl silicone oil in proportion, stirring to obtain a uniform coating mixture, and vacuum degassing the mixture to obtain a uniform coating mixture containing a self-seeping oil component; Applying an ultra-low adhesion self-penetrating oil coating: After applying a coating mixture containing a self-penetrating oil component on the pretreated substrate surface, it is placed in an oven and cured at 60-150°C for 30-120 minutes to form an ultra-low adhesion coating with both anti-stick and self-penetrating oil properties on the substrate surface.

2. The method for preparing the ultra-low adhesion coating with anti-sticking and self-oiling properties according to claim 1, characterized in that: During the substrate pretreatment process, the substrate is ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 5 to 15 minutes each time to remove surface oil and impurities, and then dried in a clean environment for later use.

3. The method for preparing the ultra-low adhesion coating with anti-sticking and self-oiling properties according to claim 1, characterized in that: In the process of preparing the coating mixture containing the self-seeping oil component, the vinyl-terminated polydimethylsiloxane prepolymer and the hydrogen-containing silicone oil are mixed at a mass ratio of 100:(8-12), a small amount of platinum catalyst is added and mixed evenly, and then the low molecular weight dimethyl silicone oil is added, and the mass fraction of the low molecular weight dimethyl silicone oil in the coating mixture is 30%-70%; The molecular weight of the vinyl-terminated polydimethylsiloxane prepolymer is 5,000 to 20,000 g / mol; the hydrogen content of the hydrogen-containing silicone oil is 0.5 to 2.0 mmol / g; the platinum content of the platinum catalyst is 0.1 to 2 wt%; and the viscosity of the low molecular weight dimethyl silicone oil is 5 to 200 cSt.

4. The method for preparing the ultra-low adhesion coating with anti-sticking and self-oiling properties according to claim 1, characterized in that: In the process of preparing the coating mixture containing the self-penetrating oil component, the stirring temperature is 20-40° C., the stirring time is 0.5-2 hours, the vacuum degree of vacuum degassing is 1-100 Pa, and the degassing time is 10-60 minutes.

5. The method for preparing the ultra-low adhesion coating with anti-sticking and self-oiling properties according to claim 1, characterized in that: The coating method in the process of coating the ultra-low adhesion self-penetrating oil coating is one of spin coating, spray coating, scraper coating, dip coating or screen printing; In the process of coating the coating mixture containing the self-penetrating oil component on the surface of the pretreated substrate, the substrate is placed in an environment with a vacuum degree of 1-100 Pa for degassing for 5-30 minutes before coating; the coating thickness after coating is 5-100 μm.

6. The method for preparing the ultra-low adhesion coating with anti-sticking and self-oiling properties according to claim 1, characterized in that: The material of the substrate is one of stainless steel, aluminum alloy, glass, ceramic, silicon wafer, polycarbonate, polypropylene or polyimide.

7. An ultra-low adhesion coating with anti-sticking and self-oil seepage properties prepared by the method for preparing an ultra-low adhesion coating with anti-sticking and self-oil seepage properties as claimed in any one of claims 1 to 6.

8. Use of the ultra-low adhesion coating with anti-stick and self-oil permeation properties as claimed in claim 7 in improving the adhesion of silicone rubber coating.

9. The use according to claim 8, characterized in that: The ultra-low adhesion coating with anti-sticking and self-oiling properties as claimed in claim 7 is introduced between the substrate and the silicone rubber coating.

10. The use according to claim 9, characterized in that: In the process of introducing the ultra-low adhesion coating between the substrate and the silicone rubber coating, the coating mixture of the self-penetrating oil component is first coated on the pretreated substrate surface, the coating thickness is 5 to 50 μm, and after degassing for 5 to 30 minutes under a vacuum condition of 1 to 100 Pa, the interface layer containing the self-penetrating oil component is obtained after curing at 60 to 150° C. for 1 to 15 minutes. Thereafter, a silicone rubber material with a thickness of 5 to 100 μm is coated on the interface layer, and the silicone rubber coating with high bonding strength is obtained after curing at 100 to 150° C. for 30 to 120 minutes.

Citation Information

Patent Citations

  • Preparation method of reinforced organosilicon heat-conducting fin

    CN105017542A

  • Lubricating organic-silicon anti-icing coating prepared by ''one-step method'' and preparation method of coating

    CN108587453A

  • Self-lubricating addition type liquid silicone rubber, and preparation method and application thereof

    CN110499032A

  • Self-oil-seepage low-permanent compression deformation liquid silicone rubber and preparation method thereof

    CN111234534A

  • Organic silicon automobile leather capable of being bitten by mouths of infants and preparation method of organic silicon automobile leather

    CN117002117A

Cited By

  • Preparation method of liquid-like coating based on dynamic phase separation

    CN120682719A